Assessing the Functioning of Land Rental Markets in Ethiopia - Deininger, Klaus; Ali, Daniel Ayalew; Alemu, Tekie (2012)
Although a large theoretical literature discusses the possible inefficiency of sharecropping contracts, empirical evidence on this phenomenon has been ambiguous at best. Household-level fixed-effect estimates from about 8,500 plots operated by households that own and sharecrop land in the Ethiopian highlands provide support for the hypothesis of Marshallian inefficiency. At the same time, a factor adjustment model suggests that the extent to which rental markets allow households to attain their desired operational holding size is limited. Our analysis points toward factor market imperfections (no rental for oxen), lack of alternative employment opportunities, and tenure insecurity as possible reasons underlying such an outcome. They suggest that, rather than worrying only about Marshallian inefficiency, attention to the broader environment and policy framework within which producers can adjust to their optimum operational area will be warranted.